(untitled) (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2021)
This text aims to present some reflections, from a bibliographical research, about the epistemological fundaments of the Gramscian theory, its approaches to the Marxism and its commitment with other lifestyle. Initially some important milestones in Antonio Gramsci’s life history and his intellectual influences are discussed. Then, based on Karl Marx and Antonio Gramsci’s work, some assumptions from the Historical-Dialectical Materialism and the social and political emergency for other hegemony are shown. The discussions have some guiding concepts, such as: “Education”, “State”, “hegemony” and “philosophy of praxis”. The theoretical reference which sustains the arguments is the Historical-Dialectical Materialism. Keywords: Gramsci. Historical-Dialectical Materialism. Hegemony. Philosophy of praxis.